2009
DOI: 10.2169/internalmedicine.48.1614
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Comparative Study of Piperacillin and Sulbactam/Ampicillin in Patients with Community-Acquired Bacterial Pneumonia

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, we underscore rational use of these antibiotics to prevent emergence of resistant strains of H. influenzae and other bacteria, including Pseudomonas aeruginosa [18] . For these reasons, piperacillin may be an appropriate first choice to treat CAP during influenza season [19] .…”
Section: Discussionmentioning
confidence: 99%
“…However, we underscore rational use of these antibiotics to prevent emergence of resistant strains of H. influenzae and other bacteria, including Pseudomonas aeruginosa [18] . For these reasons, piperacillin may be an appropriate first choice to treat CAP during influenza season [19] .…”
Section: Discussionmentioning
confidence: 99%
“…The general clinical efficiency of piperacillin therapy in these patients was similar to that of ampicillin-sulbactam therapy. The previous study by Seki et al concluded that piperacillin was effective in the treatment of pneumonia and proposed piperacillin as a first-line treatment for community-acquired pneumonia [ 36 ]. From the results of our study, piperacillin cannot be recommended as a first-line treatment for patients with pneumonia caused by Haemophilus species because of its relatively high resistance rate and lower sensitivity rate according to our susceptibility testing results.…”
Section: Discussionmentioning
confidence: 99%
“…The search for RCTs yielded 5,495 titles. After applying inclusion and exclusion criteria, 43 RCTs were included in the final analysis (Figure ): two trials of CAP‐C; three of mixed CAP‐C and CAP‐H, 20 of CAP‐H, two of mixed CAP‐H and HCAP, three of HCAP, six of HAP, five of VAP, and two of HAP and VAP . Two CAP‐H trials targeted a priori an elderly population …”
Section: Resultsmentioning
confidence: 99%